The Carrier of the Mark / Leigh Fallon - Fallon, Leigh
Instantly drawn to a mysterious, alluring boy in her class, teenaged Megan, an American living in Ireland, discovers that they are linked by a supernatural destiny that gives them powers Megan never knew she possessed.